Demokrasi dan Legalitas Mantan Narapidana dalam Pemilihan Kepala Daerah dan Pemilihan Umum - Muhammad Anwar Tanjung; Retno Saraswati (Jurnal Hukum IUS QUIA IUSTUM, 2018)
The focus of this study was on the decision of the Constitutional Court number 4/PUU-VII/2009 and decision number 14-17/PUU-V/2007 which legitimize former prisoners as regional head and legislative candidates. This study aimed to analyze the legality of former prisoners to participate in an election and the efforts to be made after the Constitutional Court's decisions in terms of building democracy in Indonesia. This study used normative research method with statute and conceptual approaches. The results of this study concluded that first, a former prisoner has constitutional right as a candidate in an election that is a part of non-derogable rights except by a court decision that has permanent legal force. Some efforts to build democracy are made by issuing regulations that technically explain the decisions of the Constitutional Court for former prisoners who will participate in an election as well as severe sanctions for the violations, and involving the supervision of election organizing committee in the nomination process.